Rare and contemporary dance as cultural mediators within a b-learning mode: the fuzzy logic perspective - Sofia B. Dias; Sofia J. Hadjileontiadou; José A. Diniz; Stelios Hadjidimitriou; Vasileios Charisis; Leontios J. Hadjileontiadis (Italian Journal of Educational Technology, 2018)
The concept of cultural mediation via undergraduate courses in rare and contemporary dance within a blended learning (b-learning) mode is approached here through a fuzzy logic (FL)-based.modelling perspective. Students’ online interaction on the Moodle Learning Management System (LMS).during such b-learning courses was logged over an entire academic year, and the resulting data were.analysed using FL, in order to estimate users’ LMS Quality of Interaction (QoI). Using documental.analysis, the pedagogical design strategies per semester were transformed into concept maps and related.with the dynamically (per week) estimated QoIs. The latter were used by the teachers at the end of the.first semester to reflect upon and update their pedagogical planning, so as to enhance QoI in the second.semester. The results show the beneficial role of QoI in supporting more dynamic design of educational.scenarios, yet considering the inherent tendencies/attitudes of users’ interaction within different cultural.expressions.